The Waterboy - Simonds, Robert 1964-; Giarraputo, Jack; Herlihy, Tim 1966-; Sandler, Adam 1966-; Coraci, Frank 1966-; Bates, Kathy 1948- .; Balk, Fairuza 1974- . (Burbank, California Touchstone Home Video, 1999)
Just an oddball mama's boy from the back bayous of Louisiana, Bobby Boucher never wanted anything more than to quench the thirst of the dehydrated athletes who treat him like dirt! But when Coach Klein makes call that allows Bobby to finally stand up for himself, it unleashes a torrent of bottled-up frustration...and exposes a talent for tackling that transforms him from a meek "water distribution engineer" to the hardest hitter ever to roam the gridiron!
Executive producer, Adam Sandler ; Co-producer, Ira Shuman ; Director of photography, Steven Berstein.
Adam Sandler, Kathy Bates, Fairuza Balk, Jerry Reed, Henry Winkler.
VHS format.
In English.
Keywords: Football -- Drama; Comedy films